Pedophile hunters and performing masculinities online - Hussey, Emma (Deviant behavior, 2022)
Pedophile hunting - abetted by digital technologies - has spread rapidly, resulting in detrimental outcomes, including suicides of hunters’ targets. The scant research on these groups adopts a functionalist argument that they have emerged to fill a security deficit - to undertake work that police are incapable of due to resource and skill deficits in policing the cybersphere. This paper adopts a critical approach to argue that the expressive nature of such activities must be incorporated into explanations for their rapid spread across the globe. Specifically, pedophile hunting can be understood as embodying the performance of masculinities in the digital realm.